Diseño fotovoltaico sostenible para la red eléctrica en la Plaza del Fundador – ULVR - Franco Burgos, Lady Helena (2025)
This thesis addresses the design and implementation of a sustainable photovoltaic system for the Founder's Plaza of the Universidad Laica Vicente Rocafuerte (ULVR) in Guayaquil, Ecuador. The main objective of this project is to contribute to the environmental sustainability of the university, reduce its carbon footprint, and promote the use of renewable energy on campus. The study focuses on the evaluation of the solar potential of the plaza, the technical design of the photovoltaic system, the selection of equipment and materials, the economic and environmental analysis of the implementation, and the proposal of a management and maintenance plan for the system. A detailed analysis of solar radiation in the area is carried out, the photovoltaic system is sized to cover part of the plaza's energy demand, and different solar panel configurations and technologies are evaluated......